2017
DOI: 10.5114/ada.2017.69313
|View full text |Cite
|
Sign up to set email alerts
|

Morphea in Middle Anatolia, Turkey: a 5-year single-center experience

Abstract: IntroductionMorphea, also referred to as localized scleroderma, is a rare fibrosing skin disorder of undetermined cause.AimWe report our single-center experience with morphea.Material and methodsThe study included 53 patients who were diagnosed with morphea by histopathology in our department between 2010 and 2015. Study data were collected retrospectively from the records of morphea patients.ResultsThe study included 53 patients (38 women, 15 men), and median age at onset was 39.0 (range: 8–85) years. Thirty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…(18) determined it as 3.5 and Leitenberger (19) as 3.7. Although the ratio of girls/boys was found to be between 2.4 and 1.2 in other studies performed in our country, we found it to be 3.9 in our 39 cases, which is comparable with the most available literature (11,12).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…(18) determined it as 3.5 and Leitenberger (19) as 3.7. Although the ratio of girls/boys was found to be between 2.4 and 1.2 in other studies performed in our country, we found it to be 3.9 in our 39 cases, which is comparable with the most available literature (11,12).…”
Section: Discussionsupporting
confidence: 88%
“…The rate of affected females is 2-4 times higher than affected males in morphea (2,4,5). The most comprehensive one of the multi-centered studies up to this date belongs to Zulian Although the ratio of girls/boys was found to be between 2.4 and 1.2 in other studies performed in our country, we found it to be 3.9 in our 39 cases, which is comparable with the most available literature (11,12).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…We included 20 studiesone RCT, four cohort studies, and 15 case series studiescomprising a total of 644 patients; 14 of these studies involved children (30,35,41,51,56,61,67,69,(129)(130)(131)(132)(133)(134). One RCT on juvenile morphea was found (Zulian et al) (51) that enrolled 70 patients (46 in the MTX group, 24 in the placebo group).…”
Section: Morphea (M Localized Scleroderma)mentioning
confidence: 99%